PENGARUH KEPERCAYAAN DAN PENGETAHUAN TENTANG ZAKAT TERHADAP MINAT MASYARAKAT MEMBAYAR ZAKAT DI BADAN AMIL ZAKAT NASIONAL KABUPATEN BEKASI - Sianturi, Roni; Setya Prayoga, Anggi (STEBI Global Mulia Cikarang, 2022)
During the last 4 years there has been an increase in receipt of zakat funds at the Bekasi Regency National Amil Zakat Agency. The increase in receipt of zakat funds for 4 years is not in accordance with the potential for zakat in Bekasi Regency. Based on the 2021 zakat data outlook of the National Amil Zakat Agency (BAZNAS), the total potential for zakat in Indonesia in 2021 is IDR 327.6 trillion, in West Java it is IDR. 36.1 trillion and in Bekasi Regency 3.7 trillion (BAZNAS, Puskas, 2022). If seen from these data, it can be said that there is a gap, because of the total potential for zakat in Bekasi Regency, the zakat collected is only Rp. 15.7 billion or only 0.4% of the total receipt of zakat funds from Bekasi Regency in 2021. This study aims to find out how the influence of trust on people's interest in paying zakat at the Bekasi Regency National Amil Zakat Agency, to find out how the influence of knowledge about zakat on people's interest in paying zakat at the Bekasi Regency National Amil Zakat Agency, and to find out how the influence of trust and knowledge about zakat simultaneously on the public's interest in paying zakat at the Bekasi Regency National Amil Zakat Agency. In this study, researchers used the theory of trust according to Izzatunnafsi Kurniawan (2019) to build trust, seven core values are needed, namely openness, honesty, integrity, competence, sharing, respect and accountability. The theory of knowledge about zakat according to Itaq Pangestu (2016) there are several indicators to find out knowledge about zakat, including whether or not zakat is known, knowledge about whether zakat is necessary or not, knowledge about zakat law, knowledge about the amount of zakat and the purpose of zakat being ordered. Theory of interest according to Muklish Muhammad Nur and Zulfahmi (2018) there are three indicators that can be used to measure interest, namely encouragement from within the individual, social motives and emotional factors. This study uses a quantitative approach with primary data. The population in this study was the adult community of Kampung Babakan Banten, Sumberurip Village, Pebayuran District with ages from 18 to 40 years of 335 people. The sample in this study was taken from the population using the Slovin formula, so there were 182 respondents. The results of this study indicate that partially trust has a significant effect on people's interest in paying zakat at the Bekasi Regency National Amil Zakat Agency, because the t-value is 3.078 > the t-table value is 1.973 with sig. 0.002 <0.05. Knowledge of zakat has no significant effect on people's interest in paying zakat at the Bekasi Regency National Amil Zakat Agency, because the t-value is 0.751 < the t-table value is 1.973 with sig. 0.453 > 0.05. Meanwhile, trust and knowledge about zakat simultaneously have a significant effect on people's interest in paying zakat at the Bekasi Regency National Amil Zakat Agency, because the calculated F value is 4.912 > the F table value is 3.05 with sig. 0.008 < 0.05.